Resepsi Sivitas Akademik terhadap Kampanye Pengelolaan Sampah pada Akun Instagram @banksampah.upnvj - Tineke Permata Sari; Arya Yudha Prakoso; Hadi Prabowo; Yani Hendrayani (Ranah Research : Journal of Multidisciplinary Research and Development, 2026)
This study analyzes the reception of the academic community at UPN "Veteran" Jakarta (UPNVJ) toward the waste management campaign conducted through the Instagram account @banksampah.upnvj. Employing a qualitative approach with a reception study method, this research operationalizes Stuart Hall's encoding-decoding model to map the meaning-making positions of six informants representing three layers of the academic community: lecturers, students, and educational and cleaning staff. Data were collected through semi-structured in-depth interviews using a content stimulus technique. The results showed that three informants (50%) were in the dominant-hegemonic reading position, two informants (33.3%) were in the negotiated reading position, and one informant (16.7%) was in a position approaching a negotiated-oppositional reading. These findings indicate that the UPNVJ Waste Bank Instagram campaign successfully built message legitimacy among the cleaning staff and some directly involved students. However, it has not been able to evenly reach all layers of the academic community, particularly lecturers and educational staff who remained unexposed to the account. Effective environmental communication requires a multi-platform strategy that extends beyond the boundaries of the Instagram ecosystem.